EFFICIENT MATRIX ELEMENT CALCULATIONS FOR THE SPECTRAL DOMAIN METHOD APPLIED TO SYMMETRICAL MULTICONDUCTOR TRANSMISSION LINES - Coetzee, J.C. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The spectral domain method has proved to be a suitable analytical tool for the characterization of open, symmetrical planar structures. The method requires the repeated calculation of matrix elements, which each involves the time-consuming process of numerical integration over an infinite range. In this paper, suitable basis functions for the expansion of electric surface currents on strips or electric fields in slots, are provided. It is also shown how the use of these basis functions makes possible the efficient and rapid calculation of the matrix elements. [Vol. 9, No. 1 (1994), pp 40-50]